All or nothing : how Trump recaptured America - Wolff, Michael, 1953- (Crown, 2025)
This book "takes readers on a journey accompanying Donald Trump on his return to power as only Michael Wolff, the foremost chronicler of the Trump era, can do it. As Trump cruelly and swiftly dispatches his opponents, heaps fire and fury on the prosecutors and judges who are pursuing him, and mocks and belittles anyone in his way--including the President of the United States--this becomes not just another election but perhaps, both sides say, the last election. ... What soon emerges is a split screen reality: on one side, a picture that could not be worse for Trump: an inescapable, perhaps mortal legal quagmire; on the other side, an entirely positive political outlook: overwhelming support within his party, ever-rising polling numbers, and lackluster opposition. ... Threading a needle between tragedy and farce, the fate of the nation, the liberal ideal, and democracy itself, All or Nothing paints a ... portrait of a man whose behavior is so unimaginable, so uncontrolled, so unmindful of cause and effect, that it defeats all the structures and logic of civic life. And yet here, in one of the most remarkable comebacks in American political history, Trump is victorious"--